Structure of an inverted duplication formed as a first step in a gene amplification event: implications for a model of gene amplification. - Passananti, C (1987)
Inverted duplications have been observed to be a common feature of gene amplification in mammalian cells and appear to be generated as a primary event in the amplification process (Ford et al., 1985; Ford and Fried, 1986). The structural features of the amplified inverted duplication, containing the polyoma virus oncogene middle T-antigen, were analysed in transformed 3B rat cells. No unusual sequences such as transposition elements were detected at the site of the inversion. The inversion was generated by a simple illegitimate recombination event in which only a single nucleotide directly at the point of the inversion cannot be accounted for from the sequence of the two parental strands. Possible structural (hairpin formation) and sequence (rich AT) features may have been involved in the illegitimate recombination event at the inversion join. In the cellular DNA near one of its joins with polyoma virus DNA an unusual sequence of 198 bp composed of 99 consecutive purine-pyrimidine pairs has been detected. A model for the generation of amplified DNA containing inverted duplications is proposed.